An analysis of income from staking crypto assets paid to a non-resident in terms of the South African Income Tax Act No. 58 of 1962, and a tax treaty established on the OECD Model Tax Convention - Jordaan, Frederik Ernst (Department of Commercial Law, 2025)
The increasing prominence of crypto asset transactions has brought their tax implications into focus. This thesis explores whether returns from Decentralized Finance (DeFi) transactions, particularly staking activities, can be classified as interest for tax purposes under South African law and international tax treaties, specifically the 2017 OECD Model Tax Convention on Income and Capital (OECD Model). A comprehensive legal analysis, supported by an exemplar, is used to determine how these innovative financial transactions align with existing legal frameworks both domestically and internationally. South Africa, consistent with other jurisdictions, does not classify crypto assets as fiat currency or legal tender. Current guidance suggests that income derived from crypto asset transactions is subject to general tax rules, potentially taxed as ordinary income or capital gains. This paper assesses whether the returns from staking crypto assets resemble interest and could trigger the application of South Africa's withholding tax on interest (WTI). Section 24J of the Income Tax Act provides a non-exhaustive list of items considered as interest in relation to financial and lending arrangements, with the underlying principal in common law being that interest is compensation for the advancement of credit. Interestingly, across the definition under section 24J and the common law definition, the mutual understanding is that interest is not confined to arise from money or currency and can take various forms in substance. Under the OECD Model, interest is similarly defined as income from debt claims, with no explicit reference to money or currency. By contrast, the UK acknowledges similarities between DeFi returns and traditional interest but maintains that interest can only arise from money or currency, thus excluding DeFi returns from being considered as interest. This thesis examines whether staking returns from DeFi can be classified as interest under Article 11 of the OECD Model and whether tax treaties can reduce or eliminate South Africa's WTI on such returns. It concludes that staking returns could potentially be taxed as interest under South African law but underlines the need for clearer regulatory guidance at both national and international levels to address the growing complexities posed by DeFi.